The Persistence of Feudalism in the Films of Alice Rohrwacher - Bertland, Alexander U. (Quaderni d'Italianistica)

(untitled) (Iter Press, 2025)
In Lazzaro Felice (2018), Alice Rohrwacher juxtaposes premodern Italian feudalism with contemporary capitalism to question whether conditions for agrarian workers are improving under the latter. This essay gives content to this comparison by discussing how Italian feudalism historically functioned not only as an economic system but also as a judicial system. Feudal nobles had the power and responsibility to enforce the law in their fiefs, and they used that authority to control and exploit their vassals. Lazzaro Felice’s depiction of contemporary democracy suggests that it has not fundamentally altered the judicial power of the wealthy and questions whether the powerful can still use the judicial system to control and exploit agrarian workers. In this light, Lazzaro Felice and Rohrwacher’s earlier Le Meraviglie (2014) can be seen as encouraging viewers to think about legal reform to help agrarian workers. This essay also examines Rohrwacher’s directorial strategies for depicting the sharp divide between the perspective of agrarian workers who care for nature and the perspective of entrepreneurs who see nature as a source of profit.